2020
DOI: 10.1002/cne.24858
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain network development in children following prenatal methamphetamine exposure

Abstract: Brain imaging studies in children with prenatal methamphetamine exposure (PME) suggest structural and functional alterations of striatal, frontal, parietal, and limbic regions. However, no longitudinal studies have investigated changes in structural connectivity during the first 2 years of formal schooling. The aim of this study was to explore the effects of PME on structural connectivity of brain networks in children over the critical first 2 years of formal schooling when foundational learning takes place. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 52 publications
(66 reference statements)
1
18
0
Order By: Relevance
“…Prenatal exposure to MA affects the brain development of neonate and children. Previous neuroimaging studies [55,56,[58][59][60][61][62][63][64][65][66] have identified the changes of subcortical and cortical brain volumes and thickness which were determined and calculated automatically by using magnetic resonance imaging. For this preliminary study, we global intracerebral brain volumes, subcortical brain structure, and cerebellum.…”
Section: Subcortical and Cortical Brain Volumes And Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…Prenatal exposure to MA affects the brain development of neonate and children. Previous neuroimaging studies [55,56,[58][59][60][61][62][63][64][65][66] have identified the changes of subcortical and cortical brain volumes and thickness which were determined and calculated automatically by using magnetic resonance imaging. For this preliminary study, we global intracerebral brain volumes, subcortical brain structure, and cerebellum.…”
Section: Subcortical and Cortical Brain Volumes And Thicknessmentioning
confidence: 99%
“…Cloak et al [55] found that lower diffusion in white matter which may reflect more compact axons or greater dendritic or spine density of children prenatally exposed to MA. The changes of white matter microstructure and structural connectivity between MA-exposed and unexposed children aged 6 to 8 years were identified by Roos et al [61,62], they found that prenatal MA exposure disrupted integrity of tracts traversing frontal, striatal and limbic regions [61] and decreased connectivity in frontal and limbic hubs, increased connectivity in the superior parietal cortex and striatum [62]. Importantly, Warton et al [63,64] found that prenatal MA exposure leads to changes of corticostriatal white matter and fiber networks in neonates.…”
Section: Brain Network Connectivitymentioning
confidence: 99%
“…However, diffusion tensor imaging (DTI) studies have reported that prenatal exposure to methamphetamine is more associated with white matter microstructure alterations (12). Alteration such as diffusion measures in white matter connections and reduction of fractional anisotropy (FA) in several connections between the striatum and midbrain (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Based on some studies, mood di culties, cognitive de ciencies, and chronic behavioral abnormalities are increased in PME children in childhood and maybe adolescence (13). Early detection of vulnerable children and psychological caring may prevent severe social and psychiatric problems in the next generation.…”
mentioning
confidence: 99%
“…However, diffusion tensor imaging (DTI) studies have reported that prenatal exposure to methamphetamine is more associated with white matter microstructure alterations (12). Alteration such as diffusion measures in white matter connections and reduction of fractional anisotropy in several connections between the striatum and midbrain (12,13).…”
mentioning
confidence: 99%